Information ergonomics in eHealth - Jussi Okkonen (Finnish Social and Health Informatics Association, 2020)
Maintaining performance in digital ubiquitous work environment is increasingly dependent on the quality of physical, cognitive and organizational ergonomics of work. Since digital work environment is the reign of most knowledge workers, there is a need to elaborate the study of work ergonomics by devoting attention to the issue of information ergonomics. In health care digitalisation has affected operation model thoroughly. It has affected how information is recorded, managed and distributed. Novel service models powered by digital channels offer now ways to practice professions as well as there are several outcomes regarding the whole service area. This paper is a summary of four research projects on how digitalisation affects knowledge work and how working is (re)shaped by sociotechnical work environments with reflection to eHealth. The conclusion in the paper underlines the digital transformation shaping the lives of knowledge workers. Discussion on how sociotechnical reshapes both individual and organisations, not to mention extended organisations. As the working practices as well as conventions and norms dictate the daily flow people have developed digital coping strategies. Paper also discusses the future of information ergonomics research in health care as way to find normative result for enhancing work in sociotechnical environment. technical environment.